Prevalence and Correlates of Postpartum Depression (PPD) In India: Literature Review-Based Study - Upalkar, Yamini (Journal of Neonatal Surgery, 2025)
Background: Despite being the most prevalent consequence, postpartum depression is abnormal, impacting the majority of new moms and playing a major role in maternal morbidity. Objective: This research work aims to examine the prevalence and analyse the correlates of PDD in India. Methodology: A search of PsycINFO, Google Scholar, and PubMed (2015-2023) yielded studies examining the prevalence of postpartum depression, family health, maternal mental health, and the links between postpartum depression and both socioeconomic status and psychological factors. Result: The most significant elements that lead to PDD are those that are associated with biology, psychology, and society. A mother's mental health was most negatively impacted by her incapacity or short duration of nursing in the immediate postpartum period. Premature birth, adverse birth experiences, (biological variables), an infant's excessive crying, low maternal self-efficacy, and a lack of support from partners, family, and the community are other factors. Conclusion: There is strong evidence that postpartum depression hinders both the parents and children's ability to thrive in their new environments. To prevent negative consequences, it appears crucial to detect and treat postpartum depression promptly.